Comparison of the Cheapest Insertion Heuristic Algorithm, Christofides Algorithm, and Nearest Neighbor Algorithm for Determining Hospital Tours in Bandar Lampung City - Thomas Juliansyah; Riska Aulia Putri; Roro Ayu Martinez; Muslim Ansori; Wamiliana Wamiliana (Jurnal Komputasi, 2025)
Determining the optimal route is one of the important aspects in planning the distribution of health services, especially in emergency conditions in Bandar Lampung City. This study compares three algorithms for solving tour problems, namely Cheapest Insertion Heuristic, Nearest Neighbor (NN), and Christofides Algorithm, in determining the fastest tour to a number of hospitals. Calculations were performed manually and also implemented using the Python programming language. The results obtained show that manually and using Python programming, the Cheapest Insertion Heuristic algorithm produced 152 minutes, the Nearest Neighbour algorithm 142 minutes, and the Christofides Algorithm 147 minutes.